Budaya dan Kinerja Organisasi Lembaga Amil Zakat - Purwanti, Ari (BINA' AL-UMMAH, 2020)
This article examines how far the organizational culture has significant influences on the performance of an organization. The results of research on LAZNAS Yatim Mandiri Lampung explain that the organizational culture and employee performance that was built, developed and inherited by this institution were based on the TRUST (True, Responsibility, Upgradeble, Service Excelent, Trust) value and FAST (Fathanah, Amanah, Shiddiq, Tabliqh) values. The cultural values above have strong driving forces in improving organizational performance and has direct impacts on the economic performance of the organization in the long term.